Assessment of motion of colonic contents in the human colon using MRI tagging. Issue 9 (25th April 2017) - Pritchard, S. E.; Paul, J.; Major, G.; Marciani, L.; Gowland, P. A.; Spiller, R. C.; Hoad, C. L.
Abstract: Background: We have previously reported a non‐invasive, semi‐automated technique to assess motility of the wall of the ascending colon (AC) using Magnetic Resonance Imaging. This study investigated the feasibility of using a tagged MRI technique to visualize and assess the degree of flow within the human ascending colon in healthy subjects and those suffering from constipation. Methods: An open‐labeled study of 11 subjects with constipation and 11 subjects without bowel disorders was performed. MRI scans were acquired fasted, then 60 and 120 minutes after ingestion of a 500 mL macrogol preparation. The amount of free fluid in the small and large bowel was assessed using a heavily T2‐weighted MRI sequence. The internal movement of the contents of the AC was visualized using a cine tagged MRI sequence and assessed by a novel analysis technique. Comparisons were made between fasting and postprandial scans within individuals, and between the constipation and control groups. Key Results: Macrogol significantly increased the mobile, MR visible water content of the ascending colon at 60 minutes postingestion compared to fasted data (controls P =.001, constipated group P =.0039). The contents of the AC showed increased motion in healthy subjects but not in the constipated group with significant differences between groups at 60 minutes ( P <.002) and 120 minutes ( P <.003). Conclusions and inferences: This study successfully demonstrated the use of a novel MRI tagging technique to visualize and assess the motion of ascending colon contents following a 500 mL macrogol challenge. Significant differences were demonstrated between healthy and constipated subjects. Abstract : This article reports the first successful use of an MRI tagging technique to show differences in the movement of chyme in the ascending colon of subjects with constipation and healthy controls following a 500 mL macrogol stimulus. These differences were assessed using a novel analysis technique.